Analysis and Characterization of a Moisture Sensor for South-American Wood Species - Avalos, Mariel (2024)
This article outlines the analysis and characterization of a moisture sensor designed specifically for wood species, including uncommon ones not found in Europe and North America. The profiling of these varieties has been devised to gauge the moisture levels within a wooden specimen through the utilization of a non-intrusive capacitance sensor, deriving values from the inherent dielectric characteristics of the material. Diverse wood species underwent thorough characterization, and a proposed multiple regression model aims to facilitate the precise calibration of the sensor concerning South American timber varieties and other uncommon species not found in Europe and North America.